Triptycene‐Roofed Quinoxaline Cavitands for the Supramolecular Detection of BTEX in Air. Issue 10 (16th February 2016) - Bertani, Federico; Riboni, Nicolò; Bianchi, Federica; Brancatelli, Giovanna; Sterner, Elizabeth S.; Pinalli, Roberta; Geremia, Silvano; Swager, Timothy M.; Dalcanale, Enrico
Abstract: Invited for the cover of this issue are the groups of Enrico Dalcanale at the University of Parma and Timothy M. Swager at Massachusetts Institute of Technology alongside collaborators at the University of Trieste. The image depicts the capture of aromatic hydrocarbons molecules by the ditrypticene quinoxaline cavitand that was employed as fiber coating for solid‐phase microextraction monitoring in air. Read the full text of the article at10.1002/chem.201504229 . Abstract : "Like the ghost trap in the Ghostbusters movie, our triptycene‐roofed quinoxaline cavitand is able to capture BTEX pollutants from air." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3312 ff. (DOI:10.1002/chem.201504229 ).